Politeness in Anggoro Ihankâ€™s "Pak Guru Inyong" Comic - Ni Putu Venia Marelda Artha; I Nyoman Muliana; Ni Wayan Kasni (RETORIKA: Jurnal Ilmu Bahasa, 2019)
This research aims to explore the accomplishment of politeness principles and the violation on the politeness principles in â€œPak Guru Inyongâ€ comic. This research was carried out using qualitative type of research. The data were collected by reading and taking notes from a 40 episode of the comic texts written by Anggoro Ihank and uploded in a Webstoon Aplication. The application was reached in Line application via android. The data were analyzed by using the theory of general strategy of politeness by Leech. The results of the analysis show that there are ten general strategies of politeness accomplished by the characters in the comic: generosity maxim, tact maxim, approbation maxim, and modesty maxim, obligation S to O maxim, obligation O to S maxim, agreement maxim, opinion maxim, sympathy maxim and feeling reticence maxim. There are five maxims violated by Pak Inyong, such as the maxims of generosity, approbation, modesty, agreement, feeling reticence.